Akademicka droga i działalność naukowa historyka wychowania Wiesława Jamrożka (1954–2021) na poznańskim uniwersytecie - Brenk, Mikołaj; Nowak-Kluczyński, Konrad (Pedagogika Społeczna Nova, 2026)
The article presents the figure of an outstanding historian of education who died prematurely on April 2, 2021, head of the Department of History of Education at the Faculty of Educational Studies at Adam Mickiewicz University in Poznań – Professor Wiesław Jamrożek. His interests and research focused on the history of educational thought and practice, primarily in the nineteenth and twentieth centuries. They concerned such issues as: theory and methodology of the history of education; creators of the Polish history of education; ideology and educational activity of Polish political and social movements in the 19th and 20th centuries; education of women in the nineteenth and twentieth centuries; Polish pedagogical thought of the nineteenth and twentieth centuries; civic education in Poland in the 19th and 20th centuries; school reforms in Poland (from the 18th to the end of the 20th century); upbringing in the Polish family of the nineteenth and twentieth centuries; history of adult education in Poland in the 19th and 20th centuries; birth and development of social work in Poland.